The Hourglass: A Conceptual Framework for the Transport of Biologically Active Compounds from Agricultural Landscapes1. (April 2014) - Kolok, Alan S.; Sellin Jeffries, Marlo K.; Knight, Lindsey; Snow, Daniel D.; Bartelt‐Hunt, Shannon L.
Abstract Recent research has suggested that the fate of biologically active compounds (BACs) originating from point sources such as wastewater treatment plants is fundamentally different from that of similar compounds released from nonpoint sources through runoff from agricultural landscapes. Downstream from wastewater treatment plants, BACs will degrade via a variety of mechanisms; however, their concentration in the water adjacent to the point of discharge may not decrease over time, as the compounds are continually released. In contrast, in agricultural systems, BACs are episodically introduced to surface water during snowmelt and rainstorm events, and under these circumstances, may be found in water for only hours or days after a storm event. Recent research in our laboratories as well as others, has suggested that sediments play an important role in the persistence of herbicides and steroids in watersheds after nonpoint source loading events. Conceptually, the sediment serves as both a sink and a source, equilibrating with BACs during storm events then slowly releasing them back into the water over time, long after the initial pulse of chemicals has moved downstream.